Confronting Poverty Economic Hardship in the United States - Rank, Mark Robert (SAGE Publications, Incorporated, 2021)
Confronting Poverty is a text that addresses four fundamental questions about economic hardship in the U.S: (1) What is the nature, prevalence, and characteristics of poverty; (2) Why does poverty exist; (3) What are the effects and consequences of poverty upon individuals and the wider society; and (4) How can poverty be reduced and alleviated?